Water as an Independent Taste Modality - Rosen, Andrew M.; Roussin, Andre T.; Di Lorenzo, Patricia M. (Frontiers in Neuroscience, 2010)
To qualify as a “basic” taste quality or modality, defined as a group of chemicals that taste alike, three empirical benchmarks have commonly been used. The first is that a candidate group of tastants must have a dedicated transduction mechanism in the peripheral nervous system. The second is that the tastants evoke physiological responses in dedicated afferent taste nerves innervating the oropharyngeal cavity. Last, the taste stimuli evoke activity in central gustatory neurons, some of which may respond only to that group of tastants. Here we argue that water may also be an independent taste modality. This argument is based on the identification of a water dedicated transduction mechanism in the peripheral nervous system, water responsive fibers of the peripheral taste nerves and the observation of water responsive neurons in all gustatory regions within the central nervous system. We have described electrophysiological responses from single neurons in nucleus of the solitary tract (NTS) and parabrachial nucleus of the pons (PbN), respectively the first two central relay nuclei in the rodent brainstem, to water presented as a taste stimulus in anesthetized rats. Responses to water were in some cases as robust as responses to other taste qualities and sometimes occurred in the absence of responses to other tastants. Both excitatory and inhibitory responses were observed. Also, the temporal features of the water response resembled those of other taste responses. We argue that water may constitute an independent taste modality that is processed by dedicated neural channels at all levels of the gustatory neuraxis. Water-dedicated neurons in the brainstem may constitute key elements in the regulatory system for fluid in the body, i.e. thirst, and as part of the swallowing reflex circuitry.